Synthesis of Organochalcogen Compounds using Non‐Conventional Reaction Media. Issue 2 (16th February 2016) - Perin, Gelson; Alves, Diego; Jacob, Raquel G.; Barcellos, Angelita M.; Soares, Liane K.; Lenardão, Eder J.
Abstract: Organochalcogen compounds (containing S, Se and Te) are interesting either for use as an intermediate in the synthesis of complex molecules or for the exploitation of their biological properties. The growing in the number of papers on the synthesis and application of organochalcogen compounds has been accompanied by a concern about how they are prepared. Here, we provide a comprehensive and updated review on recent synthetic methods available for their synthesis using alternative solvents or solvent‐free conditions and non‐classical energy sources (microwaves irradiation, sonochemistry and mechanochemistry). Organized in fourteen sections, this review brings the more than one hundred alternative methods described so far to access organic compounds containing selenium, tellurium and sulfur. Abstract : The recent advances in the synthesis of organochalcogen compounds using alternative reaction media, as alternative solvents, solvent‐free conditions and non‐classical energy sources are described.